2019
DOI: 10.1371/journal.pone.0215577
|View full text |Cite
|
Sign up to set email alerts
|

The right to health as the basis for universal health coverage: A cross-national analysis of national medicines policies of 71 countries

Abstract: Persistent barriers to universal access to medicines are limited social protection in the event of illness, inadequate financing for essential medicines, frequent stock-outs in the public sector, and high prices in the private sector. We argue that greater coherence between human rights law, national medicines policies, and universal health coverage schemes can address these barriers. We present a cross-national content analysis of national medicines policies from 71 countries published between 1990–2016. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 21 publications
1
18
0
1
Order By: Relevance
“…While several studies have delved into the relationship between healthcare and human rights [4][5][6][7][8][9][10][11][12][13], none examines the knowledge and awareness about the linkage between human rights and healthcare among patients, healthcare providers and members of civil society in Bangladesh. The current study is an attempt to ll this gap.…”
mentioning
confidence: 99%
“…While several studies have delved into the relationship between healthcare and human rights [4][5][6][7][8][9][10][11][12][13], none examines the knowledge and awareness about the linkage between human rights and healthcare among patients, healthcare providers and members of civil society in Bangladesh. The current study is an attempt to ll this gap.…”
mentioning
confidence: 99%
“…In this study we observed that some civil law countries (Ecuador, Ukraine) prescribe the structure, function, and responsibilities of these bodies in national law. Common law countries (Ghana, Philippines, South Africa) construct these types of public health infrastructure in policy rather than law [ 58 ]. For example, the national pharmaceutical policy in Ghana establishes the National Medicines Selection Committee and the National Medicines Price Committee; the latter committee sets prices for all reimbursed medicines [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Future research should investigate the effectiveness of legal interventions at enhancing patient-level knowledge about their medicine’s entitlements and lower-priced alternatives. Further studies should also explore which conditions and factors facilitate health providers, public authorities, and economic operators to provide the information about medicines pricing and benefits that they are required to [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…These principles are: the right to health (n ≤2003 , = 0/32 policies, n ≥2004 = 13/39 policies, p = 0.000), government financing (n ≤2003 , = 6/32 policies, n ≥2004 = 18/39 policies, p = 0.015), efficient spending/cost-effectiveness (n ≤2003 , = 14/32 policies, n ≥2004 = 29/39 policies, p = 0.009), and financial protection of vulnerable populations (n ≤2003 , = 4/32 policies, n ≥2004 = 13/39 policies, p = 0.041). Full results are reported elsewhere [55].…”
Section: National Medicines Policiesmentioning
confidence: 99%